Molybdenum – and tungsten(II) monometallic 3-(2-pyridyl)pyrazole and bimetallic 3-(2-pyridyl)pyrazolate complexes - Arroyo, Marta (2015)
Molybdenum and tungsten complexes containing the pypzH (3-(2-pyridyl)pyrazole) ligand as a chelating bidentate are prepared: [Mo(CO)(4)(pypzH)], cis-[MoBr(eta(3)-allyl)(CO)(2)(pypzH)], cis-[MoCl(eta(3)-methallyl)(CO)(2)(pypzH)], [MI2(CO)(3)(pypzH)] (M = Mo, W) from [Mo(CO)(4)(NBD)] or the adequate bis(acetonitrile) complexes. The deprotonation of the molybdenum allyl or methallyl complexes affords the bimetallic complexes [cis-{Mo(eta(3)-allyl)(CO)(2)(mu(2)-pypz)}](2) or [cis-{Mo(eta(3)-methallyl)(CO)(2)(mu(2)-pypz)}](2) (mu(2)-pypz = mu(2)-3-(2-pyridyl-kappa N-1) pyrazolate-2 kappa N-1). The allyl complex was subjected to an electrochemical study, which shows a marked connection between both metallic centres through the bridging pyridylpyrazolates.